“Producción de biomasa y rendimiento del maíz blanco duro (zea mays, L) variedad nutrimaíz, con tres dosis de humus de lombriz y su respuesta en la fijación de CO2 en la banda de shilcayo-San Martín” - Ríos Ríos, Raúl (2007)
They studied three In the present fact-finding work different humus dose versus chemical payments and an absolute witness in the Maíz Blanco Duro cultivation ( Nutrimaíz ), looking for optima! application levels of the humus. Take him to end in the Distrito of the Banda of Shilcayo, in her Fund Miraflores Universidad National De San Martín to approximately 6 kilometers urban of Tarapoto. this work's objectives were to evaluate the biomass production and the white corn•s performance hard ( Nutrimaíz ), the effect of the fertilization with three humus dose of earthworm and his answer in C02 fixing, and to accomplish an economic cost analysis - 1 benefit of the studíed treatments. The design once was used was the one with blocks completely at random ( DBCA ), which 1 consist of 5 treatments and 4 repetitions. They made following observations: germination, height Percentage of plants, ears of corn height to the harvest, performance in kílograms for hectare, vegetable biomass, carbon in the vegetable biomass, in the biomass and economic analysis The work install him the September 11 the 2006 and 1 finish the December 6 the 2007. the work's total area belonged to 512,5 m. Being treatment bigger-performance T4 of 2 986.3 Kg/Ha, having SI. net profit NPK. 397.6 and the relation 1 benefit cost it became of 1.23. Being also the T 4 the that principal obtained quantity of biomass, carbon and C02 with 25 603.5 biomass kg/ha, 11 521 NPK. 6 carbon kg/ha and C02 's 960.17 kg/ha, and the T3 ( 6 tm/ha humus ) with 25 465.1 biomass kg/ha, 11 459. 3 carbon kg/ha and C02 954.90 kg/ha.